Netnographic Insights: Unveiling Green Marketing Strategies for Business Development in Scarlett Cosmetics - Milany, Audy Putri; Santi, Ira Nuriya; Rombe, Elimawaty; Murad, Moh. Ali (International Journal of Economics Development Research (IJEDR), 2025)
In today’s world, both national and international companies are increasingly producing environmentally friendly products and services as part of their Corporate Social Responsibility (CSR) efforts, which positively impact the environment and society. Scarlett Cosmetics is one such company. This study aims to explore the green marketing strategies implemented by Scarlett Cosmetics. A virtual ethnographic approach was employed, utilizing online observation techniques with a "lurking" method on relevant platforms. The study found that Scarlett’s green marketing strategy includes: 1) the use of glass bottles to promote eco-friendly products, 2) environmental awareness campaigns through the #SayangiDiriSayangiBumi program, and 3) a commitment to sustainability. The findings suggest that Scarlett’s green marketing strategy not only enhances its brand image but also fosters increased customer satisfaction and loyalty.